2008
DOI: 10.1088/0022-3727/41/15/155312
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo calculation of backscattering factor for Ni–C multilayer system

Abstract: Auger electron spectroscopy (AES) depth profiles using the NiMVV (61 eV), CKLL (272 eV) and NiLMM (848 eV) lines were recorded for a 3 × (Ni(40 nm)/C(28 nm))/Si substrate sample. It was found that the Auger intensities corresponding to pure regions of the depth profile changed with depth. The behaviour of the change was different for the different layers and different Auger lines. The changes can be attributed to the change in the backscattering factor (BF) as the thickness of the sample changes due to the spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…[11] and the way of generating the path length in layered sample in ref. [12]. The electron trajectory is followed from its entry point into the sample until it leaves the surface or its energy reaches the cutoff energy, i.e.…”
Section: The Monte Carlo Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] and the way of generating the path length in layered sample in ref. [12]. The electron trajectory is followed from its entry point into the sample until it leaves the surface or its energy reaches the cutoff energy, i.e.…”
Section: The Monte Carlo Modelmentioning
confidence: 99%
“…The formula properly modified can be used to describe Auger current for layered sample with layers parallel to its surface [12]. However, the aim of this paper is an attempt to determine the Auger current emitted from the sample with perpendicular layers to its surface versus incident electron beam position.…”
Section: Auger Current Calculationsmentioning
confidence: 99%
“…Zommer and coworkers developed a theoretical model including simultaneously two effects: elastic scattering of Auger electrons and backscattering of the primary beam electrons. Monte Carlo (MC) simulations of both phenomena, performed for the Ni/C multilayer deposited on Si, indicated that the shape of the in‐depth AES profile is slightly different for each layer, even if identical thicknesses of analyzed layers have been assumed.…”
Section: Introductionmentioning
confidence: 99%
“…In this approximation, the electron is assumed to dissipate its energy continuously along its trajectory inside the solid. The power of the CSDA for describing electron trajectories in the MC simulations was analysed by Jablonski et al [4] and by Zommer et al [5,6]. In [6] the AES depth profiles (the Ni 61 eV, C 272 eV, Ni 848 eV transitions) were compared with those provided by the MC algorithm developed for the determination of the backscattering factor (BF) for buried layers [7].…”
Section: Introductionmentioning
confidence: 99%
“…The power of the CSDA for describing electron trajectories in the MC simulations was analysed by Jablonski et al [4] and by Zommer et al [5,6]. In [6] the AES depth profiles (the Ni 61 eV, C 272 eV, Ni 848 eV transitions) were compared with those provided by the MC algorithm developed for the determination of the backscattering factor (BF) for buried layers [7]. The agreement was excellent, though distinctly different cases were analysed: substantially different energies of Auger 0022-3727/09/195301+06$30.00 electrons and elements with rather large differences between atomic numbers.…”
Section: Introductionmentioning
confidence: 99%